Optimising the performance of a style-based investment strategy on the Johannesburg Stock Exchange to protect against a market downturn using dynamic, synthetic option-based portfolio insurance - Muller, Chris (University of Pretoria, 2015)
Dissertation (MBA)--University of Pretoria, 2014.